Medidas cautelares em face da lei 12.403/11 - Cherem, Cristiane Goulart (2013)
The present work aims to analyze the law 12.403/11, especially in view of the personal protective measures, others than prison, that became part of the criminal justice system. To achieve this purpose, was used the deductive methodology and technical literature, employing books, doctrines, scientific articles in journals, case law and legislation that involves knowledge and the subject's development. The study of the proposed topic is justified to the extent that the said law changes the paradigm of criminal procedure which focused primarily on the precautionary arrest and provisional freedom, with or without bail, setting several measures of none-jail which, if implemented effectively, tend to vent the Brazilian prison system, as well better suit the Criminal Procedure Code to the 1988 Constitution of the Federative Republic of Brazil. The precaution in criminal proceedings remains invigorated with legislative innovation, which also identifies the importance of the topic. Through the studies, it is seek to establish an overview about the possibility of efficiency of criminal procedure being adopted in the new precautionary measures. During the survey, it was found that, in general, the new law provides criminal procedural mechanisms compatible with a constitutional criminal procedure, allowing the realization of a just outcome. On the other hand, evince the need to implement the new law by the judiciary operators, otherwise, like so many other pieces of legislation become forgotten, providing a gap between theory and practice, losing great opportunity to perform a prosecution with proportionality